Obraz współczesnej Polski w refleksji literackiej Wiktora Jerofiejewa - Popiel-Machnicki, Wawrzyniec (Acta Polono-Ruthenica, 2018)
For Russian writer Victor Erofeyev Poland has always played a great role, which is visible in his private life as well as his works. The picture of Poland can be found in his novels, essay writing and interviews, which this Russian postmodern writer often willingly gives to Polish newspapers. The writer has lately overestimated his positive attitude towards our country. It has been especially visible after joining NATO and the European Union by Poland or after Smolensk catastrophe.